Taṭbīq at-Ṭarīqah al-Qiyāsiyyah Wa Uslūb NHT Bi al-Biṭṭāqah at-Takammulah Li Tarqiyah Qudrah aṭ-Ṭālibāt `Alā Fahm al-Qawā`id an-Naḥwiyyah Bi Ma`had Dār al-Iḥsān - Dewi Susanti; Moch Fajarul Falah (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2020)
Al-Qawa’id al-Nahwiyyah is one of three important elements in a language. The students should be learning Qawa’id to know the correct last line of the word in Arabic language, then to help them increase their speaking and writing well and right by a good language. So, the researcher used the Qiyasiyyah and Uslub NHT by using Bitaqah Takammulah to increase students’ achievement in comprehending Qawa’id Nahwu at Darul Ihsan School. After the researcher made the observation, the researcher found many mistakes and errors in language structure, The students expressed the error example in making some sentences (error language structure), and the technique or media in the teaching-learning process was not interesting. The purpose of the research is to know the effectiveness of the application of Qiyasiyyah and Uslub NHT by using Bitaqah Takammulah to increase students’ achievement in comprehending Qawa’id Nahwu at Darul Ihsan school, also how far the student’s response after applied it. In this research, the researcher used a true-experimental method with a post-test-only control group design. The population of this research is all the students of MTsS Darul Ihsan, consisting of 740 students, in this case, the researcher used random sampling by cluster technique and the researcher took two classes as samples and those are class 2f dan 2e. The instrument of this research is the test and questionnaire after analyzing the data, the result of this research showed that the result of ttest was higher than ttabel in a significant standard of 5% was 7,36 > 2,00. Based on the research result, the researcher concludes that the application of Tariqah Qiyasiyyah and Uslub NHT by using Bitaqah Takammulah is effective for increasing student’s achievement in comprehending Qawa’id Nahwu at Darul Ihsan boarding school.